The influence of evaluation recommendations on instrumental and conceptual uses: A preliminary analysis. (June 2018) - Bourgeois, Isabelle; Whynot, Jane
Highlights: Evaluation recommendations included in Canadian federal evaluation reports focus on relevance and effectiveness. They either propose one option and describe how it should be implemented, or a more strategic series of options. Their main focus is on program design and management as well as on performance measurement. No discernible trends were observed in terms of departmental mandate. Abstract: Evaluation recommendations are sometimes included in evaluation reports to highlight specific actions to be taken to improve a program or to make other changes to its operational context. This preliminary study sought to examine evaluation recommendations drawn from 25 evaluation reports published by Canadian federal government departments and agencies, in order to examine the evaluation issues covered and the focus of the recommendations. Our results show that in keeping with policy requirements, the evaluation recommendations focused on program relevance, effectiveness and efficiency and economy. Furthermore, a significant number of recommendations also focused on the implementation of more rigorous performance measurement strategies. The focus of the recommendations did not vary by publication date, recommendation type, and organizational sector. The findings also show that for the most part, the management responses produced as part of the broader evaluation process support the recommendations included in the report and identify specific timelines for implementation.